The place of non-invasive brain stimulation in the RANZCP clinical practice guidelines for mood disorders. (April 2021) - Fitzgerald, Paul B; Gill, Shane; Hussain, Salam; Sarma, Shanthi; Chamoli, Suneel; Weiss, Alan; Garside, David; Purushothaman, Subramanian; Fasnacht, Matthew; Simpson, Brett; Csizmadia, Tibi; Dean, Carol; et al.
Clinical practice guidelines are important documents as they have the capacity to significantly influence and shape clinical practice in important areas of therapeutics. As such, they need to be developed informed by comprehensive and quality-based systematic reviews, involve consensus deliberations representative of the appropriate experts in the field and be subject to thorough critical review. A revised clinical practice guideline for the management of patients with mood disorders was recently published under the auspices of the Royal Australian and New Zealand College of Psychiatrists. However, this clinical practice guideline was not developed in a manner that reflects the appropriate standards that should apply to clinical practice guideline development and it has critical flaws, especially as it pertains to the use of repetitive transcranial magnetic stimulation treatment for patients with depression. The revision of the college clinical practice guideline has explicitly removed clear and unequivocal evidence-based recommendations that were found in a previous version of the clinical practice guideline and replaced these with consensus-based recommendations. However, the consensus-based recommendations were developed without consultation of the appropriate expert body within the college and contradict the scientific literature. There is substantive and unequivocal evidence supporting the antidepressant use of repetitive transcranial magnetic stimulation in the treatment of patients with depression and its use after a patient with depression has failed a limited number (typically around two) of antidepressant medication trials. Readers should refer to the college Professional Practice Guidelines for repetitive transcranial magnetic stimulation published in 2018 for thorough information about the use of this important new treatment.